Reciprocal communication of perivascular epicardial adipose tissue and coronary atherogenesis. (25th November 2020) - Wildauer, M; Honold, S; Beyer, C; Senoner, T; Stuehlinger, M; Friedrich, G; Feuchtner, G; Plank, F
Abstract: Purpose: Perivascular epicardial adipose tissue (PEAT) has been linked to underlying coronary artery disease (CAD) and proposed to modulate adjacent atherosclerotic plaque formation. In vitro and ex vivo studies support bilateral influence of adipose tissue and vessel wall. Therefore, we quantified PEAT volume and composition and its dynamics in a low coronary risk patient cohort with a semi-automate software in serial CT exams. Methods and materials: We retrospectively included 120 patients (27% females) from a tertiary care hospital who underwent serial cardiac CT angiographies with a low cardiovascular risk profile. All coronary CTs were evaluated in a standardized approach: epicardial adipose tissue (EAT) volume and attenuation was quantified in total, in the atrioventricular (RCA, LCX) or interventricular (LAD) sulcus and in a 5mm radius for each coronary artery (PEAT). Coronary plaques were quantified using a semi-automated software and compared to progression, stability of regression between the two scans. The measurements were compared on a per-patient and per-vessel basis between plaque-naïve and diseased vessels. Results: Of 120 patients (32% female), 59.2%) had atherosclerotic plaque formation. After 36 months mean follow-up, 22 (18.3%) showed a CAD regression plaques, 39 (32.5%) had stable coronary arteries and 49 (40.8%) progressive CAD. Total EAT volume decreased by −15.6±37.2 mm 3 in the regressive group, increased by 2.7±30.6mm 3 in the stable group and by 24.3±37.1mm 3 in the progressive CAD group (p=0.003). Per-vessel analysis showed a significant decrease of perivascular EAT attenuation in patients with CAD regression (−3.8±7.6 HU) compared to CAD stable (1.2±9.1 HU) and CAD progressive patients (3.5±8.2 HU, p<0.0001). Mean sulcus EAT attenuation did not show a significant change at follow-up (p=0.135) Conclusion: Epicardial adipose tissue volume is mutually changing with the progression or regression of coronary artery disease. Perivascular but not epicardial attenuation levels correlated to adjacent plaque and support a direct bilateral influence. Funding Acknowledgement: Type of funding source: None